HectoSTAR mu LED Optoelectrodes for Large-Scale, High-Precision In Vivo Opto-Electrophysiology - Voroslakos, Mihaly; Kim, Kanghwan; Slager, Nathan; Ko, Eunah; Oh, Sungjin; Parizi, Saman S.; Hendrix, Blake; Seymour, John P.; Wise, Kensall D.; Buzsaki, Gyorgy; Fernandez-Ruiz, Antonio; Yoon, Euisik (Wiley-VCH Verlag, 2022)
Dynamic interactions within and across brain areas underlie behavioral and cognitive functions. To understand the basis of these processes, the activities of distributed local circuits inside the brain of a behaving animal must be synchronously recorded while the inputs to these circuits are precisely manipulated. Even though recent technological advances have enabled such large-scale recording capabilities, the development of the high-spatiotemporal-resolution and large-scale modulation techniques to accompany those recordings has lagged. A novel neural probe is presented in this work that enables simultaneous electrical monitoring and optogenetic manipulation of deep neuronal circuits at large scales with a high spatiotemporal resolution. The "hectoSTAR" micro-light-emitting-diode (mu LED) optoelectrode features 256 recording electrodes and 128 stimulation mu LEDs monolithically integrated on the surface of its four 30-mu m thick silicon micro-needle shanks, covering a large volume with 1.3-mm x 0.9-mm cross-sectional area located as deep as 6 mm inside the brain. The use of this device in behaving mice for dissecting long-distance network interactions across cortical layers and hippocampal regions is demonstrated. The recording-and-stimulation capabilities hectoSTAR mu LED optoelectrodes enables will open up new possibilities for the cellular and circuit-based investigation of brain functions in behaving animals.